Loss of Kynurenine 3-Mono-oxygenase Causes Proteinuria - Korstanje, Ron; Deutsch, Konstantin; Bolanos-Palmieri, Patricia; Hanke, Nils; Schroder, Patricia; Staggs, Lynne; Braesen, Jan H.; Roberts, Ian S. D.; Sheehan, Susan; Savage, Holly; Haller, Hermann; Schiffer, Mario (Journal of the American Society of Nephrology, 2016)
Changes in metabolite levels of the kynurenine pathway have been observed in patients with CKD, suggesting involvement of this pathway in disease pathogenesis. Our recent genetic analysis in the mouse identified the kynurenine 3-mono-oxygenase (KMO) gene (Kmo) as a candidate gene associated with albuminuria. This study investigated this association in more detail. We compared KMO abundance in the glomeruli of mice and humans under normal and diabetic conditions, observing a decrease in glomerular KMO expression with diabetes. Knockdown of kmo expression in zebrafish and genetic deletion of Kmo in mice each led to a proteinuria phenotype. We observed pronounced podocyte foot process effacement on long stretches of the filtration barrier in the zebrafish knockdown model and mild podocyte foot process effacement in the mouse model, whereas all other structures within the kidney remained unremarkable. These data establish the candidacy of KMO as a causal factor for changes in the kidney leading to proteinuria and indicate a functional role for KMO and metabolites of the tryptophan pathway in podocytes.
EVALuna2:34555